A Pilot Randomized Control Trial: Testing a Transitional Care Model for Acute Psychiatric Conditions. (September 2014) - Hanrahan, Nancy P.; Solomon, Phyllis; Hurford, Matthew O.
OBJECTIVE: People with multiple and persistent mental and physical health problems have high rates of transition failures when transferring from a hospital level of care to home. The transitional care model (TCM) is evidence-based and demonstrated to improve posthospital outcomes for elderly with physical health conditions, but it has not been studied in the population with serious mental illness.METHOD: Using a randomized controlled design, 40 inpatients from two general hospital psychiatric units were recruited and randomly assigned to an intervention group ( n = 20) that received the TCM intervention that was delivered by a psychiatric nurse practitioner for 90 days posthospitalization, or a control group ( n = 20) that received usual care. Outcomes were as follows: service utilization, health-related quality of life, and continuity of care.RESULTS: The intervention group showed higher medical and psychiatric rehospitalization than the control group ( p = .054). Emergency room use was lower for intervention group but not statistically significant. Continuity of care with primary care appointments were significantly higher for the intervention group ( p = .023). The intervention group's general health improved but was not statistically significant compared with controls.CONCLUSIONS: A transitional care intervention is recommended; however, the model needs to be modified from a single nurse to a multidisciplinary team with expertise from a psychiatric nurse practitioner, a social worker, and a peer support specialist. A team approach can best manage the complex physical/mental health conditions and complicated social needs of the population with serious mental illness.